2016
DOI: 10.3892/or.2016.4772
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of WNT5B promotes COLO 205 cell migration and invasion through the JNK signaling pathway

Abstract: WNT5B is a member of the WNT family that has been reported to be overexpressed in a variety of cancer cell lines and tissues, including colorectal cancer (CRC). However, the potential roles of WNT5B in tumorigenesis have not been reported. In the present study, the WNT5B gene was transfected into CRC cells and generated a COLO 205 cell line with stable overexpression of WNT5B. MTT, wound healing and Transwell assays showed that overexpression of WNT5B significantly increased cell proliferation, migration and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…We also examined the expression of WNT5A and WNT5B, as they are also non-canonical Wnts with altered expression in CRC (Table S1b). WNT5A was low/undetectable in all cell lines and WNT5B was high in LoVo cells and moderate/low in the other cell lines (Figure S8b), consistent with previous studies [25,26]. Western blots were carried out to confirm the WNT11 mRNA results at the protein level.…”
Section: Resultssupporting
confidence: 89%
“…We also examined the expression of WNT5A and WNT5B, as they are also non-canonical Wnts with altered expression in CRC (Table S1b). WNT5A was low/undetectable in all cell lines and WNT5B was high in LoVo cells and moderate/low in the other cell lines (Figure S8b), consistent with previous studies [25,26]. Western blots were carried out to confirm the WNT11 mRNA results at the protein level.…”
Section: Resultssupporting
confidence: 89%
“…JNK can rearrange the actin cytoskeleton, thereby regulating the planar polarity of the cell to promote invasion and metastasis of the tumor. JNK can also increase the secretion of MMPs in CRC cells to promote their metastasis ( 25 27 ). Therefore, we speculated that COL1A1 may promote CRC cell migration through the WNT/PCP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Wnt5b rs2010851 polymorphism predicts a high risk of tumor recurrence in patients with advance-stage colon cancer (107). Overexpression of Wnt5b increased the proliferation, migration, and invasion of CRC cells through activating the non-canonical Wnt/JNK signaling (50). Meanwhile, Wnt5b exosome released from CRC cells could stimulate the migration and the proliferation of other cancer cells in a paracrine manner (108).…”
Section: Wnt16mentioning
confidence: 99%
“…Until recently, Bauer et al found two isoforms of Wnt5a protein with opposite functions in cancers ( 105 ), and a subsequent study proved that the simultaneous reactivation of the downregulated Wnt5a-long mRNA isoform and knockdown of the upregulated Wnt5a-short mRNA isoform could induce the apoptosis of CRC cells by silencing the expression of β-catenin, providing a reasonable explanation for the obscure role of Wnt5a in CRC previously ( 106 ). Wnt5b plays a pivotal role during embryonic gut development ( 51 ), and its expression level is increased significantly in ulcerative colitis and CRC samples ( 49 , 50 ). Moreover, the Wnt5b rs2010851 polymorphism predicts a high risk of tumor recurrence in patients with advance-stage colon cancer ( 107 ).…”
Section: Roles Of Wnts In Tumorigenesis and The Progression Of Crcmentioning
confidence: 99%